Psychological Reflections on Ismail al-Faruqi’s Life and Contributions - Malik Badri (International Institute of Islamic Thought, 2014)
Perhaps I am one of the few persons who can contemplate deeply upon the psychosocial factors that shaped Ismail al-Faruqi’s life and helped transform him into a great Muslim thinker. First, as a psychologist, I could clearly see from his career, as well as from his matchless linguistic ability and long personal discussions with him, that he was a highly intelligent and creative person with a rare gift for perceiving a holistic picture of seemingly unrelated aspects. Second, I am now an old man who lived in Lebanon and Jordan from the early 1950s until the late 1960s, interrupted only by the two years I spent in England pursuing my doctorate. I earned my BA and MA at the American University of Beirut (AUB) and then taught there after obtaining my doctorate. I am therefore well acquainted with the culture of Lebanon, Syria, and Jordan, as well as with AUB’s academic and social life, during those years. Al-Faruqi joined AUB at an early age and was greatly influenced by what it had to offer. Third, I was privileged to have long discussions and friendly talks with him during my visits to the United States and his visit to Saudi Arabia. I first met him in Indianapolis in 1976 at the international annual conference organized by the Muslim Students Association (MSA) and the Association of Muslim Social Scientists (AMSS). We had long academic discussions on Islamization and the future of Islamic psychology. It was his idea that Muslim psychologists in North America should form a psychology branch within the AMSS. I spent three months in Indianapolis, sharing the same house with the renowned scholar Taha Jabir al-Alwani. During these months I was asked to ...